Conhecimento e percepções da diversidade local de mamíferos por comunidades rurais na sub-bacia do rio Guareí, sudoeste de São Paulo - Rocha, Ismael Correa (Universidade Federal de São Carlos, 2024)
Ethnozoology focuses on elucidating the human-wildlife relationship, perceptions and human knowledge acquired about Earth's faunal. Ethnozoological studies on mammals in Brazil are relatively scarce and mainly address inventories, hunting and other uses, leaving aside aspects of human perception of this faunal group. The Guareí River sub-basin, located in the southwest of the state of São Paulo, has characteristics that value the recovery of local ethnozoological knowledge, with rural communities amid relatively preserved natural environments and rich fauna. The present study investigated the knowledge and perceptions of the rural population about the diversity of mammals in this region. For this, semi-structured interviews were carried out, between April and June 2023, with 30 residents (10 women and 20 men) from the rural neighborhoods of Angatuba: Arealzinho, Modestos and Leites. Of the 35 mammal species with possible occurrence in the region, only the red-headed howler monkey (Alouatta guariba clamitans) was not mentioned by any of the interviewees as having been seen in the study area. The target audience carries very peculiar customs and traditions in relation to coexistence with mammals in the region. Habits such as hunting and consuming the meat of these animals are still alive in people's customs or memories, in addition to the use of meat and other parts of animals for medicinal and/or sympathetic purposes. About residents' perceptions regarding mammals, a strong interaction between them was noticed. Many revealed that they believe that animals can attack, but only when they are threatened. Some believe that animals can transmit diseases to both humans and domestic animals, in addition to bringing economic losses to the community. Finally, the interviewees showed a strong environmental awareness, realizing the importance of fauna and pointing out the potential causes of animal population decline, such as deforestation, hunting and the introduction of invasive species. The present study generated a first overview of rural communities in the Guareí River sub-basin in relation to their perceptions regarding the population dynamics of mammals in the region over time and the identification of behaviors that can be shaped with a view to conserving the species.
Knowledge and perceptions of local mammal diversity by rural communities in the Guareí river sub-basin, southwest of São Paulo
Keywords: Etnoecologia; Etnozoologia; Mastofauna; Conhecimanto tradicional; Etnoecology; Mastofauna; Traditional Knowledge; CIENCIAS BIOLOGICAS